Anthropogenic changes in land use and their consequences on rodent populations reservoirs of zoonotic viruses - Gomez, Maria Daniela (2024)
The ecology of animal host species can be altered when their habitats are modied, aecting thetransmission of their pathogens and the probability of disease risk in the human population. Predicting how zoonotic diseases emerge and spread in response to anthropogenic land use changes requires an understanding of how these changes inuence hosts and pathogens. The objective of this paper is to analyze how urbanization, agricultural intensication, and invasive species have favored the increase in population abundance of host species and the transmission of zoonotic viruses. This work seeks to synthetize research conducted from the 1990s to the present day in dierent regions of Argentina on species of rodent reservoirs of the viruses that cause Argentine Hemorrhagic Fever, Lymphocytic Choriomeningitis and Hantavirus Pulmonary Syndrome.The data collected link the ecology of their host species, Calomys musculinus, Mus musculus, and Oligoryzomys longicaudatus, to anthropogenic processes in dierent types of environments (rural, urban, peri-urban, semi-natural, and natural).